Advances in Pacific Basin business, economics and finance. Volume 6 - Lee, Cheng F.; Yu, Min-Teh (Emerald Publishing Limited, 2018)
Advances in Pacific Basin Business, Economics, and Finance is an annual publication designed to focus on interdisciplinary research in finance, economics, and management among Pacific Rim countries. All articles published are reviewed and recommended by at least two members of editorial board. Topics of interest include, but are not limited to, the following;1. Policy and management on financial markets and financial institutions; 2. Options, futures and other derivatives markets; 3. Corporate finance and investment decisions; 4. Insurance and risk management; 5. Accounting, auditing and taxation; 6. Marketing, management, and business policies of the Pacific Rim countries; 7. Interdisciplinary issues on supply chain, finance, and marketing; 8. Monetary and foreign exchange policy; 9. Income, employment and other economic policies among the Pacific Rim countries.
Prelims -- Related party transactions and institutional investors in Chinese listed companies -- Product market threat and corporate investment -- Discretionary idiosyncratic risk, firm cash holdings, and investment -- The economic cost of myopic going concern practice -- The choice of industrial diversification strategy for public listed firms in the hotel industry -- How do equity mispricing and long-term growth opportunities influence firm-level capital structure dynamics of Taiwanese publicly listed firms? -- How do board structures of Thai firms influence on different quantile levels of firm performance? -- Information security risk and costs of capital: evidence from Taiwan semiconductor companies -- The effect of institutional ownership stability on cash dividend policy: evidence from Taiwan -- Role of institutional quality on environmental Kuznets curve: a comparative study in developed and developing countries -- An empirical analysis of the impact of employment on the first birth decision for married women in Taiwan -- Index.
Includes index.
Print version record
Keywords: Pacific Area -- Economic conditions; Finance -- Pacific Area; Pacific Area -- Commerce; Pacific Area -- Foreign economic relations; Business & Economics -- Economics -- General; International economics